Severe disease presentation and poor outcomes among pediatric systemic lupus erythematosus patients in South Africa. (February 2017) - Lewandowski, L B; Schanberg, L E; Thielman, N; Phuti, A; Kalla, A A; Okpechi, I; Nourse, P; Gajjar, P; Faller, G; Ambaram, P; Reuter, H; Spittal, G; et al.
Background: Systemic lupus erythematosus (SLE) is a life-threatening multisystem autoimmune disease that is more severe in patients of African ancestry and children, yet pediatric SLE on the African continent has been understudied. This study describes a cohort of pediatric SLE (PULSE) patients in South Africa. Methods: Patients with a diagnosis of SLE (1997 American College of Rheumatology criteria) diagnosed prior to age 19 years in Cape Town, South Africa, were enrolled in this cross-sectional study from September 2013 to December 2014. Information on clinical and serological characteristics was extracted from medical records. Results were compared to a well-described North American pediatric SLE cohort. Results: Seventy-two South African patients were enrolled in the study; mean age 11.5 years; 82% were girls. The racial distribution was 68% Coloured, 24% Black, 5% White and 3% Asian/Indian. Most patients presented with severe lupus nephritis documented by renal biopsy (61%). Of patients with lupus nephritis, 63% presented with International Society of Nephrology/Renal Pathology Society class III or IV. Patients in the PULSE cohort were more likely to be treated with cyclophosphamide, methotrexate and azathioprine. The PULSE cohort had high disease activity at diagnosis (mean Systemic Lupus Erythematosus Disease Activity Index-2K (SLEDAI-2K) 20.6). The SLEDAI-2K at enrolment in the PULSE cohort (5.0) did not differ from the North American pediatric SLE cohort (4.8). Sixty-three per cent of the PULSE cohort had end organ damage with Systemic Lupus International Collaborating Clinics Damage Index (SLICC-DI) score >0 (mean SLICC-DI 1.9), compared to 23% in a previously reported US cohort. Within the PULSE cohort, nine (13%) developed end-stage renal disease with six (8%) requiring transplant, strikingly higher than North American peers (transplant rate <1%). Conclusions: The PULSE cohort had highly active multiorgan disease at diagnosis and significant disease damage at enrolment in the South African registry. South African patients have severe lupus nephritis and poor renal outcomes compared to North American peers. Our study revealed a severe disease phenotype in the PULSE cohort resulting in poor outcomes in this high-risk population.